Magnetic Resonance Elastography of kidneys: SE‐EPI MRE reproducibility and its comparison to GRE MRE. (22nd July 2019) - Gandhi, Deep; Kalra, Prateek; Raterman, Brian; Mo, Xiaokui; Dong, Huiming; Kolipaka, Arunark
Abstract : The purpose of this study is 1) to demonstrate reproducibility of spin echo‐echo planar imaging (SE‐EPI) magnetic resonance elastography (MRE) to estimate kidney stiffness; and 2) to compare SE‐EPI MRE and gradient recalled echo (GRE) MRE‐derived stiffness estimations in various anatomical regions of the kidney. Kidney MRE was performed on 33 healthy subjects (8 for SE‐EPI MRE reproducibility and 25 for comparison with GRE MRE; age range: 22–66 years) in a 3 T MRI scanner. To demonstrate SE‐EPI MRE reproducibility, subjects were scanned for the first scan and then asked to leave the scan room and repositioned again for the second (repeat) scan. Similar set‐up was used for GRE MRE as well. The displacement data was then processed to obtain overall stiffness estimates of the kidney. Concordance correlation analyses were performed to determine SE‐EPI MRE reproducibility and agreement between GRE MRE and SE‐EPI MRE derived stiffness. A high concordance correlation (ρc  = 0.95; p‐value<0.0001) was obtained for SE‐EPI MRE reproducibility. Good concordance correlation was observed (ρc  = 0.84; p  < 0.0001 for both kidneys, ρc  = 0.91; p < 0.0001 for right kidney and ρc  = 0.78; p < 0.0001 for left kidney) between GRE MRE and SE‐EPI MRE derived stiffness measurements. Paired t‐test results showed that stiffness value of medulla was significantly ( p  < 0.0001) greater than cortex using SE‐EPI MRE as well as GRE MRE. SE‐EPI MRE was reproducible and good agreement was observed in MRE‐derived stiffness measurements obtained using SE‐EPI and GRE sequences. Therefore, SE‐EPI can be used for kidney MRE applications. Abstract : Renal fibrosis is a common pathway among renal diseases, leading to the progression of chronic kidney disease. Magnetic resonance elastography (MRE) is used to diagnose fibrosis based on stiffness estimates. Our study showed excellent SE‐EPI MRE reproducibility and good agreement between SE‐EPI and GRE‐MRE. Hence, SE‐EPI MRE can be used to perform 3D kidney MRE, as it can significantly shorten scan time compared with GRE‐MRE.